The Style of Deletion in the Holy Quran Surat Al-A’raf Al-Mubarak Is a Model - Erayer, Rafid Difar (International Journal of Psychosocial Rehabilitation, 2020)
This research dealt with the method of deletion in the Holy Qur’an and Surat Al-A’raf Al-Mubarak was an applied example of this, the research was in two topics, the first in deletion is language and convention, and the reasons for deletion and its types, while the second topic was in the application of the method of deletion in the blessed surah.